"The godly person has perished from the land" (Mi 7:1–6): Micah"s lamentation of Judah"s corruption and its ethical imperatives for a healthy community living - Boloje, Blessing O. (HTS teologiese studies, 2021)
Micah 7:1–6 represents the prophet’s lamentation of the deficiency of moral value in a beloved nation. The oracle is a watershed in the Book of Micah that is aptly characterised by certain degrees of socio-economic and religious unfaithfulness, especially in privileged circumstances. The oracle unit (Mi 7:1–6) forms the darkest descriptions of degrees about the apparent moral wasteland of ancient Judah. The prophet’s metaphors are used to describe the miserable moral morass of society form a kind of compendium with a progression of thoughts and coherence of moral depravity. This article underscores that when people and society live in dishonesty and corruption, the essentially integrated spiritual-ethical-community of health and prosperity that is expected to unfold in time of covenant fidelity will eventually be reduced to poverty and despair, where people hunt each other for survival. This article explores aspects of dishonesty and corruption in the Book of Micah that are pointers to the tragic situation, analyses the various descriptions of corruption in the oracle unit and consequently examines its ethical imperatives for community living.Contribution: As a biblical, literary and theological interpretation of Micah’s oracle concerning ancient Judah’s moral morass, this article brings together moral insights that are potentially viable for making major contributions to the life of people and just social order in an economics of affluence, politics of oppression and corruption in societies.